Measurement of the turning behaviour of tethered membrane wings using automated flight manoeuvres - C. Elfert; D. Göhlich; R. Schmehl (Wind Energy Science)
Flexible membrane wings for kite sports, paragliding and airborne wind energy are highly manoeuvrable aerodynamic devices. The manoeuvrability can be quantified by the achievable turning rate of the wing and the dead time between the steering input and the actual flight dynamic response. In this paper, we present an onboard sensor system for measuring the position and orientation of a tethered membrane wing and complement this with an attached low-cost multi-hole probe for measuring the relative flow velocity vector at the wing. To ensure well-defined flow conditions and high quality of the measurement data, the wings selected for testing were towed by a vehicle with a constant speed along a straight track during periods of low ambient wind speeds. A flight control algorithm was adapted from the literature to execute automated, repeatable figure-eight flight manoeuvres and measure the steering gain and the dead time as functions of the steering input. The experimental study confirms the turning behaviour known from kite sports and airborne wind energy applications and provides reproducible quantitative data to develop and validate simulation models for flexible, tethered membrane wings.